2011
DOI: 10.1136/flgastro-2011-100023
|View full text |Cite
|
Sign up to set email alerts
|

The endoscopically normal colon: when is mapping biopsy histopathologically justifiable?: Table 1

Abstract: Objective Mapping biopsy of endoscopically normal colon is a contentious area and generates considerable work for histopathology services. Managing demand for pathological testing is a current healthcare priority. In this retrospective audit, the authors aimed to establish diagnostic yield of mapping biopsy in this specifi c subgroup and identify situations where practice could be safely streamlined. Design Cases were retrieved over a 10-month period. Histopathology results were correlated with relevant endosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In one case, the distorted mucosal histological pattern was consistent with inflammatory bowel disease. Moreover, Elliot et al reported that, among 151 patients with endoscopically normal or near normal colorectal mucosa, 14% (8 patients) had abnormal colorectal histology and two of them had histological findings indicating inflammatory bowel disease, ulcerative colitis type [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one case, the distorted mucosal histological pattern was consistent with inflammatory bowel disease. Moreover, Elliot et al reported that, among 151 patients with endoscopically normal or near normal colorectal mucosa, 14% (8 patients) had abnormal colorectal histology and two of them had histological findings indicating inflammatory bowel disease, ulcerative colitis type [ 25 ].…”
Section: Discussionmentioning
confidence: 99%